14th IEEE International Conference on Nanotechnology 2014
DOI: 10.1109/nano.2014.6968048
|View full text |Cite
|
Sign up to set email alerts
|

Review of reliability bounds for consecutive-k-out-of-n systems

Abstract: This paper reviews many lower and upper bounds for consecutive-k-out-of-n systems presented over the last three decades. The reason is a revived interest to accurately estimate the reliability of (very) large consecutive systems, where exact calculations can be challenging. Main examples are novel nanoarchitectures targeting FinFETs, nano-magnetic and molecular technologies (where accurate estimations of reliability are of high interest), as well as their associated nanoscale communications (where the reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…(3) Can we find a close approximation to F k (r, n, j) which would be more efficient than computing the number directly? Such approximations are used widely in engineering for F k (2, n, j) [11]. We offer the following conjecture that may be useful in obtaining helpful approximations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Can we find a close approximation to F k (r, n, j) which would be more efficient than computing the number directly? Such approximations are used widely in engineering for F k (2, n, j) [11]. We offer the following conjecture that may be useful in obtaining helpful approximations.…”
Section: Discussionmentioning
confidence: 99%
“…There are many useful and beautiful generalizations of this problem in both reliability theory and graph theory [7,8,9,1,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In [24], the series and parallel architectures are used to calculate reliability laws and failure rates of different alternatives for multilevel converters. Recent studies on peculiar reliability aspects of k-out-of-n systems are reported in [25]- [26].…”
Section: Extensions To the K-out-of-n Redundant Systemsmentioning
confidence: 99%
“…Such bounds have been found which are close approximations to the exact value of R(k, n; q) and which are also much easier to evaluate than the exact value of R(k, n; q). In [DB114], [BD14] and [DB214] the authors compare many such results from the 1980s to the present day.…”
Section: Introductionmentioning
confidence: 99%